Pengaruh Work Life Balance dan Burnout Terhadap Kepuasan Kerja Pada Karyawan Perbankan di Kota Palembang - Gunawan, Andi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to determine the effect of work life balance and burnout on job satisfaction among banking employees in Palembang City. The research population is banking employees in Palembang City. The samples used were employees of BCA, OCBC and Mandiri banks in Palembang City. The sample used was 110 respondents using the purposive sampling method. Data analysis techniques were carried out usin g descriptive analysis, research instrument testing, classical assumption testing, and multiple linear regression analysis.